In silico study of hyperthermia treatment of liver cancer using core-shell CoFe2O4@MnFe2O4 magnetic nanoparticles - Suleman, Muhammad; Riaz, Samia (Journal of magnetism and magnetic materials, 2020)
[Display omitted] •The core-shell MNPs are used in the hyperthermia of liver cancer in in-silico study.•The hyperthermia processes based on FEM analysis are simulated using COMSOL Multiphysics.•The temperature and concentration-dependent heat sources are studied versus constant heat source.•The CoFe2O4@MnFe2O4 MNPs are superior to the other core-shell MNPs for heat generation. Exchange coupling between a magnetically soft shell and magnetically hardcore can boost the properties of magnetic nanoparticles (MNPs) to maximize their power loss. These MNPs possess large specific loss powers than conventionally used iron oxide MNPs and application of these MNPs in hyperthermia of cancer may result in a better treatment option. In this paper, we have conducted an in-silico study to treat liver cancer using these core-shell MNPs. All the hyperthermia processes are based on the FEM model analysis of infusion of nanofluid flow, diffusion of nanofluid, heat transfer in liver tissue, and tumor thermal damage subject to initial and boundary conditions. All these processes are simulated using COMSOL Multiphysics to predict the pressure, velocity, concentration, temperature distribution, and the fraction of tumor damage during the treatment. The expressions for temperature and concentration-dependent heat sources are derived and compared with a constant heat source. The simulation results show that the concentration-dependent heat source produced a higher temperature as compared to the remaining two heat sources. Through simulations, we have succeeded to effectively treat liver cancer with maximum tumor damage and minimum collateral damage. The validity of our simulation curves of temperature versus time and temperature versus x-coordinate with pre-existing studies are excellent. Our simulations also revealed that the core-shell MNPs used in our study is superior to the other identical core-shell MNPs for better heat generation. Certainly, this research will aid cancer treatment protocols in the clinical setting.